PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN 212 MART PADAT KARYA KOTA PRABUMULIH - Mudzakir Ilyas; Fatiah Kurniasih (LA RIBA: Jurnal Perbankan Syariah, 2022)
This study aims to examine the effect of price and promotion on consumer purchasing decisions at 212 labor-intensive marts in Kota Prabumulih in 2021. The focus of this study is to find out how the effect of price and promotion on consumer purchasing decisions. This research was conducted in 212 labor-intensive marts in Prabumulih in 2021 with a total sample of 95 respondents. The data used in this study is primary data obtained directly from distributing questionnaires to respondents. The method used in this study is a quantitative method. Analysis of the data used is multiple linear regression analysis. The results of this study indicate that prices and promotions have a positive and significant effect on consumer purchasing decisions at 212 labor-intensive marts in Prabumulih in 2021. So this research can be continued and theoretically proven that prices and promotions affect purchasing decisions.